STRATEGI KOMUNIKASI PASAR PAYUNGI DALAM MEMBANGUN IMAGE PASAR KREATIF - Yemima Ika Puspitania; Zon Vanel (Universitas Prof. Dr. Moestopo (Beragama), 2021)
This research stems from researchers interested in the creative market in the city of Metro Lampung which can inspire many people with social media so that many people come to study and travel. Of course, researchers have a goal in research, namely to find out and describe what marketing communication strategies are carried out by the umbrella market in building an image as a creative market in Metro City. The research method in this study is phenomenological research which is carried out when researchers want to understand a phenomenon from a different point of view, for example from the point of view of certain individuals or groups who experience it. The data obtained in the study to determine the marketing communication strategy of the Payungi market was by using in-depth interviews, documentation and also observations of the location, the initiators of the Umbrella market, the chairman of the Umbrella market and also the seller in the Umbrella market who served as informants and tested the validity of the data. The results of this study prove that the communication strategy carried out by the umbrella market is based on marketing communication theory, namely advertising, public relations, sales promotion, events and experience, and direct sales. The researcher also recommends that marketing should be propagated through other media such as print media, newspapers, radio, billboards, banners to make it easier for the wider community who are still not familiar with social media.